The Mouse Superior Colliculus as a Model System for Investigating Cell Type-Based Mechanisms of Visual Motor Transformation - Oliveira, Ana F.; Yonehara, Keisuke (Frontiers in Neural Circuits, 2018)
The mouse superior colliculus (SC) is a laminar midbrain structure involved in processing and transforming multimodal sensory stimuli into ethologically relevant behaviors such as escape, defense, and orienting movements. The SC is unique in that the sensory (visual, auditory, and somatosensory) and motor maps are overlaid. In the mouse, the SC receives inputs from more retinal ganglion cells than any other visual area. This makes the mouse SC an ideal model system for understanding how visual signals processed by retinal circuits are used to mediate visually-guided behaviors. This Perspective provides an overview of the current understanding of visual motor transformations operated by the mouse SC, and discusses the challenges to be overcome when investigating the input-output relationships in single collicular cell types.